1998
DOI: 10.1007/s002590050293
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of 18 F-FDG PET with conventional imaging modalities (CT, MRI, US) in lymph node staging of head and neck cancer

Abstract: The aims of this study were to investigate the detection of cervical lymph node metastases of head and neck cancer by positron emission tomographic (PET) imaging with fluorine-18 fluorodeoxyglucose (FDG) and to perform a prospective comparison with computed tomography (CT), magnetic resonance imaging (MRI), sonographic and histopathological findings. Sixty patients with histologically proven squamous cell carcinoma were studied by PET imaging before surgery. Preoperative endoscopy (including biopsy), CT, MRI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
242
4
10

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(273 citation statements)
references
References 22 publications
12
242
4
10
Order By: Relevance
“…In only one of our cases, FDG-PET was performed, showing a preclinical lung inflammatory process diagnosed as pneumocystosis. In a recent study, FDG-PET scan did not detect occult tumors not detected by conventional CT/MR imaging (31).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In only one of our cases, FDG-PET was performed, showing a preclinical lung inflammatory process diagnosed as pneumocystosis. In a recent study, FDG-PET scan did not detect occult tumors not detected by conventional CT/MR imaging (31).…”
Section: Discussionmentioning
confidence: 84%
“…For ACTH-dependent differential diagnosis, patients underwent HDDST (8 mg) (14)(15)(16), desmopressin test (17,18), corticotropin-releasing hormone (CRH) test (19)(20)(21)(22)(23), growth hormone releasing peptide (GHRP)-6 test (24,25), and IPSS (26)(27)(28) with desmopressin stimulus indicated when magnetic resonance imaging (MRI) was negative for a pituitary lesion. IPSS was performed by collecting blood samples simultaneously from the inferior petrosal sinuses and a peripheral vein before and 3, 5, and 10 min after 10 mg of IV desmopressin (DDAVP, Ferring Pharmaceuticals, Limhamn, Sweden) (29 (31)(32)(33). Tumor markers, such as calcitonin, gastrin, carcinoembryonic antigen (CEA), a-fetoprotein, b human chorionic gonadotropin (bHCG), and 5-hydroxyindolacetic acid (5-HIAA), were also measured.…”
Section: Diagnosis Of Ectopic Acth Syndromementioning
confidence: 99%
“…PET has been shown to be superior to conventional imaging modalities for the detection of regional nodal metastases [18]. The increased glucose metabolism can be identified in lymph nodes infiltrated by tumor cells regardless of size criteria.…”
Section: N Stagementioning
confidence: 99%
“…Several authors have reported the use of fluorine-18 fluorodeoxyglucose positron emission tomography (FDG PET) scanning in cancer of the head and neck, both in the setting of primary staging 4 and the evaluation of patients after primary therapy. 5 -7 The promising results of these studies and the clear need for better evaluation of patients with head and neck cancer after attempted curative therapy encouraged us to evaluate the use of PET scanning in our institution in the setting of a tertiary referral center for management of head and neck cancer.…”
mentioning
confidence: 99%